PET/CT in lung cancer: Influence of contrast medium on quantitative and clinical assessment. - Behrendt FF; Temur Y; Verburg FA; Palmowski M; Krohn T; Pietsch H; Kuhl CK; Mottaghy FM; Behrendt, Florian F; Temur, Yavuz; Verburg, Frederik A; Palmowski, Moritz; et al. (European Radiology, 2012)
Objectives: To evaluate the influence of intravenous contrast medium and different contrast medium phases on attenuation correction, PET image quality and clinical staging in combined PET/CT in patients with a suspicion of lung cancer.Methods: Sixty patients with a suspicion of lung cancer were prospectively enrolled for combined (18)F-FDG-PET/CT examination. PET images were reconstructed with non-enhanced and arterial and venous phase contrast CT. Maximum and mean standardised uptake values (SUVmax and SUVmean) and contrast enhancement (HU) were determined in the subclavian vein, ascending aorta, abdominal aorta, inferior vena cava, portal vein, liver and kidney and lung tumour. PET data were evaluated visually for clinical staging and image quality.Results: SUVmax was significantly increased between contrast and non-contrast PET/CT at all anatomic sites (all P < 0.001). SUVmax was significantly increased for arterial PET/CT compared to venous PET/CT in the arteries (all P < 0.001). Venous PET/CT resulted in significantly higher SUVmax values compared to arterial PET/CT in the parenchymatous organs (all P < 0.05). Visual clinical evaluation of malignant lesions showed no differences between contrast and non-contrast PET/CT (P = 1.0).Conclusions: Contrast enhanced CT is suitable for attenuation correction in combined PET/CT in lung cancer; it affects neither the clinical assessment nor image quality of the PET images.Key Points: • Positron emission tomography combined with computed tomography is now a mainstream investigation • There has been debate about whether CT contrast agents affect PET results • Contrast-enhanced CT is satisfactory for attenuation correction in lung cancer PET/CT • Multiphase CT does not affect PET; additional unenhanced CT is unnecessary • For quantitative follow-up PET analysis, an identical PET/CT protocol is required.